Kulish V., Lashch К. Integration of verbal units of personified poetical silence images in literary discourse - Kulish V.; Lashch К. (Philological Treatises, 2020)
The article deals with the study of personified images of silence in poetical works of English authors based on the literary discourse. It describes the validity of the personification as a relevant stylistic device for the conveying of silence images. It analyzes basic (dominant and peripheral) verbal units of poetical silence in poetry and presents quantitative and percentage characteristic of their usage.